E-Learning and Economic Well-Being of Graduates: Applying the Human Capital Earning Function to Distance Education - Alzyadat, Jumah Ahmad (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The study aims to evaluate the effectiveness of e-learning in raising the income level of graduates. Based on a sample of the distance education program students in the Bachelor of Business Administration. The study applies the net present value, and regression model to estimate the Human Capital Earnings Function presented by Mincer (1974). The results showed that the NPV of the expected cost and earnings for graduates that the program will cause an improvement of the standard of living of graduates. Moreover, the regression results indicate that the most important factors affecting the expected wages are those objective factors such as experience and job stability, as they are superior to subjective factors such as marital status and age, the technical expertise comes between these two groups. The study recommends more use of modern technologies in the field of distance education, for all societies without restrictions of time or place, in order to achieve the spread of knowledge, to raise the efficiency and income of workers in the economy. Provide the opportunity for those who were unable to continue their university education, due to socioeconomic conditions.